2010
DOI: 10.1089/aid.2009.0223
|View full text |Cite
|
Sign up to set email alerts
|

IgG Subclass Profiles in Infected HIV Type 1 Controllers and Chronic Progressors and in Uninfected Recipients of Env Vaccines

Abstract: We have studied IgG subclass responses to the HIV-1 proteins gp120, gp41, p24, and Tat in individuals who control their infection without using antiretroviral drugs (HIV-1 controllers; HC) or who progress to disease (chronic progressors; CP). We also measured IgG subclass titers to gp120 in vaccinated individuals. In all cases, the IgG1 subclass dominated the overall response to each antigen. The only IgG titer that differed significantly between the HC and CP groups was to the p24 Gag protein, which was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 71 publications
9
105
0
Order By: Relevance
“…No differences were observed in antibody titer or IgG subclass distribution in either bulk or HIV-specific antibodies among the different patient populations (data not shown), consistent with previous reports (21), suggesting that these features could not account for the differences observed in ADCVI activity. In contrast, enzymatic removal of the glycan from the antibody heavy chain resulted in profound loss of ADCVI activity ( Figure 1C).…”
Section: Antiviral Effector Activity Of Antibodies From Hiv-infected supporting
confidence: 91%
See 1 more Smart Citation
“…No differences were observed in antibody titer or IgG subclass distribution in either bulk or HIV-specific antibodies among the different patient populations (data not shown), consistent with previous reports (21), suggesting that these features could not account for the differences observed in ADCVI activity. In contrast, enzymatic removal of the glycan from the antibody heavy chain resulted in profound loss of ADCVI activity ( Figure 1C).…”
Section: Antiviral Effector Activity Of Antibodies From Hiv-infected supporting
confidence: 91%
“…Analysis was performed to verify that brief acid exposure did not alter glycan composition and that gp120 was not released from the resin. Antibodies titers were determined by ELISA as described previously (21), and enrichment of gp120-specific antibodies was confirmed by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…127 Interestingly, reduced risk of infection was associated with the selective induction of HIVspecific IgG3 antibodies that exhibit a polyfunctional profile, able to simultaneously recruit ADCC, ADCP, and NK degranulation, potentially providing enhanced protection from diverse modes of HIV acquisition through a broader capacity to recruit a variety of innate immune effector cells. Similarly, spontaneous control of HIV infection is associated with the selective induction of gp120-specific IgG3 antibodies, 54 which normally decline following acute infection in noncontrollers. 128 These data strongly argue that IgG3 antibodies, despite their short serum half-life, represent a potent Fc modification able to rapidly control and clear HIVinfected cells.…”
Section: Subclassmentioning
confidence: 99%
“…Beyond Env-specific targeting approaches, a few studies have observed an enrichment of HIV Gag-specific 54 and other regulatory/accessory protein-specific antibodies 55 in subjects who durably control HIV infection in the absence of therapy. These antibodies against non-Env targets have been shown to mediate ADCC.…”
mentioning
confidence: 99%
“…77 Antigen-specific IgG3 antibodies are associated with long-term control of Plasmodium falciparum 78 and monocyte-mediated cellular inhibition of parasite growth in vitro. 79 Similarly, early appearance of chikungunya virus-specific IgG3 neutralizing antibodies is associated with clearance of the virus and long-term clinical protection.…”
Section: Correlates Of Protection-new Perspectivesmentioning
confidence: 99%